2013
DOI: 10.1101/lm.031989.113
|View full text |Cite
|
Sign up to set email alerts
|

Memory retrieval before or after extinction reduces recovery of fear in adolescent rats

Abstract: Adolescent rats exhibit impaired extinction retention compared to pre-adolescent and adult rats. A single nonreinforced exposure to the conditioned stimulus (CS; a retrieval trial) given shortly before extinction has been shown in some circumstances to reduce the recovery of fear after extinction in adult animals. This study investigated whether a retrieval -extinction procedure would reduce the recovery of extinguished fear in adolescent rats. Furthermore, the effect of the retrievalextinction sequence on fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 35 publications
3
59
1
Order By: Relevance
“…These findings demonstrate that neither the animal's age at the time of fear learning or extinction determines whether fear extinction is impaired. Rather, it appears that the impairment in extinction retention previously reported in adolescence (McCallum et al 2010;Kim et al 2011;Pattwell et al 2012;Baker et al 2013) requires both fear conditioning and extinction occur in adolescence (Fig. 5).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These findings demonstrate that neither the animal's age at the time of fear learning or extinction determines whether fear extinction is impaired. Rather, it appears that the impairment in extinction retention previously reported in adolescence (McCallum et al 2010;Kim et al 2011;Pattwell et al 2012;Baker et al 2013) requires both fear conditioning and extinction occur in adolescence (Fig. 5).…”
Section: Discussionmentioning
confidence: 78%
“…Future studies could test whether posterior PVT activation during extinction training modulates neuronal activity in the amygdala and if lesions or inactivation of the PVT during extinction improve extinction retention in AdolesCond-Ext animals. Moreover, manipulations that either improve extinction retention, such as D-cycloserine (McCallum et al 2010), or reduce renewal of extinguished fear, such as retrieval-extinction procedures (Baker et al 2013), might reduce posterior PVT MAPK activation in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the notion that the memory was replaced is yet to be shown Prevention of drug relapse by memory replacement K Goltseker et al directly in the future using ensemble/engram procedures (Cruz et al, 2013;Pfarr et al, 2015). Interestingly, several studies have recently shown that flipping the order of events in the retrieval-extinction procedure, that is, retrieving the memory after, rather than before extinction training, can prevent relapse in a similar manner to post-retrieval extinction (Baker et al, 2013;Millan et al, 2013), suggesting that the mechanisms underlying this procedure are not necessarily reconsolidation mechanisms. In the present study, however, flipping the order of the events, by retrieving the memory after, rather than before the counterconditioning training, did not block the reinstatement of cocaine seeking (Experiment 3b), further supporting our notion that the results we observed are mediated by memory reconsolidation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the memory must be retrieved to open the 'reconsolidation window', prior to any memory attenuating manipulation. However, there is evidence that a reversed protocol, in which the memory is retrieved shortly after extinction training, may also attenuate the memories and prevent the reinstatement of the target behavior (Baker et al, 2013;Millan et al, 2013). Therefore, we tested whether aversive counterconditioning followed (rather than preceded) by memory retrieval would affect the reinstatement of cocaine-seeking behavior.…”
Section: Experiments 1a and 1b: Aversive Counterconditioning During Mmentioning
confidence: 99%